2007
DOI: 10.1107/s0021889807003718
|View full text |Cite
|
Sign up to set email alerts
|

Contrast variation in X-ray and neutron scattering

Abstract: This contribution is meant to highlight some progress in those areas of contrast variation which are known to be technically more difficult but which promise interesting applications. These concern the use of the anomalous dispersion of light elements, like sulfur and phosphorus in structural studies and experiments of polarized neutron scattering from nuclear spin polarized samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Right system with matching fl uid present at it appears to the scattering experiment. , 1978Beaudry et al 1976;Williams et al 1979;Akcasu et al 1980;Jahshan and Summerfi eld 1980;Koberstein 1982;Hadziioannou et al 1982;Bates et al 1983;Hasegawa et al 1985Hasegawa et al , 1987Allen 1991;Hua et al 1994;Smarsley et al 2001;Littrell et al 2002;Connolly et al 2006;Stuhrmann and Heinrich 2007;Ruppert et al 2013;Thomas et al 2014). This is because the scattering length density for neutrons depends on the isotope, rather than just the element involved, and there is a very large difference in scattering length density between hydrogen and deuterium, and thus between H 2 O (neutron sld = -0.56 × 10 10 cm -2 ) and D 2 O (neutron sld = 6.392 × 10 10 cm -2 ).…”
Section: Contrast Matchingmentioning
confidence: 98%
“…Right system with matching fl uid present at it appears to the scattering experiment. , 1978Beaudry et al 1976;Williams et al 1979;Akcasu et al 1980;Jahshan and Summerfi eld 1980;Koberstein 1982;Hadziioannou et al 1982;Bates et al 1983;Hasegawa et al 1985Hasegawa et al , 1987Allen 1991;Hua et al 1994;Smarsley et al 2001;Littrell et al 2002;Connolly et al 2006;Stuhrmann and Heinrich 2007;Ruppert et al 2013;Thomas et al 2014). This is because the scattering length density for neutrons depends on the isotope, rather than just the element involved, and there is a very large difference in scattering length density between hydrogen and deuterium, and thus between H 2 O (neutron sld = -0.56 × 10 10 cm -2 ) and D 2 O (neutron sld = 6.392 × 10 10 cm -2 ).…”
Section: Contrast Matchingmentioning
confidence: 98%
“…(30) can be used to describe the state of the system at each time t. However, in this new density operator, we substitute the running time of the experiment, t, in place of the pulse length t p that appears in Eq. (29), which is equivalent to Eq. (30).…”
Section: Obtaining Structure Factors Of Nmr-selected Nucleimentioning
confidence: 99%
“…Dynamic nuclear polarization 24,25 (DNP) has also long been under investigation for its ability to polarize nuclei to enhance neutron scattering investigations. [26][27][28][29][30] Some of these methods may be useful for enhancing cross sections to be calculated below, as pointed out in Ref. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the large subunit of ribosome (1500 kD), measurements near phosphorous K-edge allowed separation of all three partial intensities [18]. Resonant scattering studies are also reported on freestanding liquid crystal films [19] and surfactant micellar solutions [3].…”
Section: Applications Of Asaxs To Soft Mattermentioning
confidence: 99%